PERBEDAAN FLEKSIBILITAS OTOT HAMSTRING ANTARA INDEKS MASSA TUBUH (IMT) NORMAL DAN OVERWEIGHT PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER - Mohammad Hendro Mustaqim (Jurnal Sains Riset, 2021)
Flexibility can be defined as the ability of a joint, muscle, and tendons around it to move freely and comfortably in the maximum space expected. Overweight or overweight is currently one of the world's health problems. Physical activity that is good and right really affects a person's musculoskeletal condition so that it impacts both body posture and physical fitness. This study aims to determine differences in hamstring muscle flexibility between body mass index (BMI) normal and overweight. This type of research is a descriptive analytic study with a Paired Sample T-test design. The sampling technique in this study is a non-random technique (Non-Probability Sampling). The number of samples used by 30 students consisted of 15 students with normal BMI and 15 students with overweight BMI. Data analysis using paired sample T test. The results of this study found that there was a difference in flexibility of hamstring muscles in normal and overweight BMI before and after heating with P-values in the normal and overweight BMI group of 0,000 so that it can be said that No there is a relationship between BMI with hamstring muscle flexibility.Keywords: Flexibility, hamstring muscles, Overweight